Predictors of Death in Severe New Coronavirus Infection in Children - Yu. S. Аleksandrovich; D. V. Prometnoy; P. I. Mironov; K. V. Pshenisnov; P. E. Anchutin; E. D. Teplyakova (Вестник анестезиологии и реаниматологии, 2021)
Currently, in pandemic settings, the new coronavirus infection is the leading cause of adult fatalities and may cause death of children with comorbidities.The objective of the study is to identify predictors of the fatality of the new coronavirus infection in children.Subjects and Methods. 230 patients with the new coronavirus infections were examined. The main group of 94 patients with severe COVID-19, the fatal outcome occurred in 25 (26.6%) children. The comparison group consisted of 126 children with a moderate degree of severity, and there were no lethal outcomes.Results. Children older than 10 years of age (43%) prevailed in the study cohort. Every fifth patient in the main group suffered from shock, and 79 (84%) children had failure of two or more systems/organs. The presence of pronounced manifestations of the disease was associated with a 20-fold increase in the probability of a severe course of COVID-19 (OR = 0.04). Involvement of two organs and systems doubled the risk of death. An acceptable discriminatory ability of the pSOFA score for predicting COVID-19 outcomes in children was identified: sensitivity 83%, specificity 61%, cut-off point 5.6 points.Conclusion. Predictors of death in severe new coronavirus infection in children include failure of two or more organs and systems, acute renal injury and the pSOFA score above 5.